Role of German-Speaking Europeans In the Development of Socio-Economic, Political and Scientific Life of Turkestan In the Xix - Early Xx Centuries - Elmurodovich, Rakhimov Bektosh; Bakayevna, Yakubova Mukhtaram (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the activities of German-speaking Europeans in Central Asia. An attempt was made to highlight their role in the socio-economic and scientific life of Turkestan. Much attention was paid to the results of research of European scientists in the region in XIX – beginning of XX century. Undoubtedly the Great Geographical Discoveries were sensational events of the new time, but despite this XIX century is estimated by contemporaries as a new period of geographical discoveries. Along with scientific expeditions to the North and South poles, the study of the internal territories of the African continent, penetration into Central Asia have identified peculiar features of the period under study.